Since the beginning : interpreting Genesis 1 and 2 through the ages - Greenwood, Kyle (Grand Rapids. MI, Baker Academic, 2018)
Few passages in the Hebrew Bible have been subject to more scrutiny than Genesis 1 and 2. In this volume, a diverse international team of experts guides readers through interpretations of the Genesis creation stories throughout history, inviting them to consider perspectives from the earliest times to the present. The book offers an accurate description of how these chapters have been read through the centuries, explaining each interpretive approach in its own terms. Each chapter includes sidebars and suggestions for further reading.
Old Testament reverberations of Genesis 1-2 / Kyle R. Greenwood -- Interpretations of Genesis 1-2 in Second Temple Jewish literature / Michael D. Matlock -- New Testament appropriations of Genesis 1-2 / Ira Brent Driggers -- Early rabbinic interpretations of Genesis 1-2 / Joel S. Allen -- Interpretations of Genesis 1-2 among the Ante-Nicene Fathers / Stephen O. Presley -- Interpretations of Genesis 1-2 among the Nicene and Post-Nicene Fathers / C. Rebecca Rine -- Medieval Jewish interpretations of Genesis 1-2 / Jason Kalman -- Medieval Christian interpretations of Genesis 1-2 / Timothy Bellamah, OP -- Interpretations of Genesis 1-2 among the Protestant reformers / Jennifer Powell McNutt -- Rediscovery of the ancient Near East and its implications for Genesis 1-2 / David T. Tsumura -- Post-Darwinian interpretations of Genesis 1-2 / Aaron T. Smith.
Includes bibliographical references (pages 271-287) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc. -- History; Criticism, interpretation, etc; History